Model predictive direct flux vector control of multi three-phase induction motor drives - Rubino, Sandro; Bojoi, Radu; Odhano, Shafiq Ahmed; Zanchetta, Pericle (IEEE, 2018)
A model predictive control scheme for multiphase induction machines, configured as multi three-phase structures, is proposed in this paper. The predictive algorithm uses a Direct Flux Vector Control scheme based on a multi three-phase approach, where each three-phase winding set is independently controlled. In this way, the fault tolerant behavior of the drive system is improved. The proposed solution has been tested with a multi-modular power converter feeding a six-phase asymmetrical induction machine (10kW, 6000 rpm). Complete details about the predictive control scheme and adopted flux observer are included. The experimental validation in both generation and motoring mode is reported, including open-winding post-fault operations. The experimental results demonstrate full drive controllability, including deep flux-weakening operation.